2017
DOI: 10.1364/boe.8.001271
|View full text |Cite
|
Sign up to set email alerts
|

Heart structural remodeling in a mouse model of Duchenne cardiomyopathy revealed using optical polarization tractography [Invited]

Abstract: Abstract:We investigated the heart structural remodeling in the mdx4cv mouse model of Duchenne cardiomyopathy using optical polarization tractography. Whole heart tractography was obtained in freshly dissected hearts from six mdx4cv mice. Six hearts from C57BL/6J mice were also imaged as the normal control. The mdx4cv hearts were significantly larger than the control hearts and had significantly higher between-subject variations in myofiber organization. While both strains showed classic cross-helical fiber or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Polarization‐sensitive OCT, which provides additional contrast by measuring changes in the polarization state of light as it passes through a medium, has also been used to provide additional sensitivity to fiber organization . OCT imaging of myofiber orientation in mouse hearts has been used to describe changes in fiber organization with respect to cardiomyopathy, infarction and aging . While it was shown in this study that tissue features could only be identified by OCT in shallow regions under thin endocardium, the use of optical clearing or serial sectioning could make it possible to generate highly detailed, transmural, large scale image maps for understanding myofiber structure and adipose distributions in the ex vivo setting.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Polarization‐sensitive OCT, which provides additional contrast by measuring changes in the polarization state of light as it passes through a medium, has also been used to provide additional sensitivity to fiber organization . OCT imaging of myofiber orientation in mouse hearts has been used to describe changes in fiber organization with respect to cardiomyopathy, infarction and aging . While it was shown in this study that tissue features could only be identified by OCT in shallow regions under thin endocardium, the use of optical clearing or serial sectioning could make it possible to generate highly detailed, transmural, large scale image maps for understanding myofiber structure and adipose distributions in the ex vivo setting.…”
Section: Discussionmentioning
confidence: 92%
“…While this study focused on adipose tissue and fiber orientation, it is also possible for OCT to provide features corresponding to fibrosis, as has been described in prior OCT studies. 8,11 Previously, OCT has also been used to describe myofiber orientation within animal models, ex vivo, [28][29][30][31][32][33][34][35][36][37] with some studies incorporating optical clearing 30,34 or serial sectioning 37 methods to improve imaging depth. Polarization-sensitive OCT, which provides additional contrast by measuring changes in the polarization state of light as it passes through a medium, 38 has also been used to provide additional sensitivity to fiber organization.…”
Section: Future Applications Of Cardiac Octmentioning
confidence: 99%
“…Additionally, optical clearing or serial sectioning could be applied to improve imaging depth for ex vivo studies. Tissue properties as identified from OCT could also be correlated to clinical disease, and the identification of fibrotic regions could be improved by the use of polarization‐sensitive OCT . Automatic identification of different tissue types can also be improved, with expansion of the adipose tissue detection algorithm to other tissue types and quantification of the detection accuracy over large regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of OCT for imaging the heart wall has also been gaining interest, where OCT may similarly be able to provide detailed structural information on pathological and remodeled tissues. OCT has been used to characterize myofiber arrangement related to heart damage and remodeling in small animal models . Recently, OCT imaging of the human heart has also been explored, identifying features of the cardiac conduction system , endocardial scar, fibrosis and adipose tissue .…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in the following cited Invited Review and Invited Research articles in this issue, remarkable strides have since been made in OCT technology encompassing novel light sources [2], imaging system architectures [3,4], and sample/patient interface technologies including endoscopic [5], catheter-based [6], intra-operative [7], adaptive-optic [8][9][10], computational [11] and microscope-based [12] implementations. Functional extensions of OCT have been developed featuring polarization-based [13], Doppler [14], elastographic [15], tractographic [16], spectroscopic [17,18] multi-modal [19] and angiographic [8,20,21] contrast, the latter of which has taken on particular current excitement and topically comprises the plurality of articles published in this Issue. Clinical applications of OCT have been developed in dozens of medical specialties, led by its most mature applications in ophthalmology and cardiology, where OCT has become a clinical standard of care and is now performed in an estimated 30 million OCT imaging procedures per year [22].…”
mentioning
confidence: 99%